Let's shape again: the concerted molecular action that builds the pollen tube - ÇETİNBAŞ GENÇ, ASLIHAN (SPRINGER, 2022)
Key message The pollen tube is being subjected to control by a complex network of communication that regulates its shape and the misfunction of a single component causes specific deformations. In flowering plants, the pollen tube is a tubular extension of the pollen grain required for successful sexual reproduction. Indeed, maintaining the unique shape of the pollen tube is essential for the pollen tube to approach the embryo sac. Many processes and molecules (such as GTPase activity, phosphoinositides, Ca2+ gradient, distribution of reactive oxygen species and nitric oxide, nonuniform pH values, organization of the cytoskeleton, balance between exocytosis and endocytosis, and cell wall structure) play key and coordinated roles in maintaining the cylindrical shape of pollen tubes. In addition, the above factors must also interact with each other so that the cell shape is maintained while the pollen tube follows chemical signals in the pistil that guide it to the embryo sac. Any intrinsic changes (such as erroneous signals) or extrinsic changes (such as environmental stresses) can affect the above factors and thus fertilization by altering the tube morphology. In this review, the processes and molecules that enable the development and maintenance of the unique shape of pollen tubes in angiosperms are presented emphasizing their interaction with specific tube shape. Thus, the purpose of the review is to investigate whether specific deformations in pollen tubes can help us to better understand the mechanism underlying pollen tube shape.
Keywords: Ca2+; Cell wall; Cytoskeleton; GTPase; Phosphoinositides; Pollen tube morphology; Reactive oxygen species; Tip growth; CELL-WALL DEPOSITION; IN-VITRO GERMINATION; TIP GROWTH; NICOTIANA-TABACUM; PROTEIN-KINASE; NITRIC-OXIDE; PECTIN METHYLESTERASE; DEPOLYMERIZING FACTOR; PHOSPHATIDIC-ACID; CALCIUM GRADIENT